Arikel Riview: Pegaruh Pemerian Resusitasi Cairan pada Pasien Gawat Darurat dengan Syok Hypovolemik - Andariningtyas Putri Febriati; Eni Nuraeni; Firlie Bastia Putty Zahra; Nadya Yundasari; Neng Feri Fajarwati; Adam Permana; Tria Alfina Damayanti; Nia Yuniarsih (Peneliti.net, 2023)
Hypovolemic shock in the medical world still ranks fairly high, the cause of this shock is generally caused by loss of intravascular fluid volume, in an emergency with cases of hypovolemic shock the medical staff at the initial stage will carry out the process of applying the ABC principles or handling disorders of the airway, breathing and circulation immediately because this is the main problem there is interference with blood perfusion to the tissues, if this principle has been carried out then fluid resuscitation is carried out to maintain fluid volume in the blood, this study describes the management of fluid resuscitation in emergency patients with hypovolemic shock, fluid resuscitation is carried out with a liquid description in the form of crystalloid fluid and colloid acquisition which aims to maintain fluid volume in the blood, the literature search method is carried out in several journals so that information and data can be used as a comparison of results so that data can be obtained. management of fluid resuscitation in emergency department patients with hypovolemic shock, namely that patients can be treated quickly and accurately and patients can return in a stable condition.